Socio-Demographic Characteristics of Abdominal Tuberculosis Patients attended at Tertiary Care Hospital in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: The socio-demographic profiles may vary among the abdominal tuberculosis patients. Objectives: The purpose of the presents study was to see the socio-demographic characteristics of abdominal tuberculosis patients.Methodology: This descriptive cross-sectional study was conducted in the Department of Surgery of Rajshahi Medical College Hospital, Rajshahi, Bangladesh from January 2014 to December 2015 for two years. This study included 100 patients who were admitted in surgery units of Rajshahi Medical College Hospital, Rajshahi, Bangladesh who were diagnosed as abdominal tuberculosis with or without associated pulmonary or nodal TB. Both male and female patients of any age except pediatric age group irrespective of nutritional and socio-economic status were included in study population. The details of demographic variables like age, sex, residence and so one were recorded in a data collection sheet.Results: A total number of 100 cases of abdominal tuberculosis patients were recruited for this. Among the 100 cases 52% was within 20 to 30 years of age. The male and female ratio was 2.45:1. Maximum cases (68.0%) were living in rural area. About 82 cases were from lower socio-economic group.Conclusion: In conclusion young adult male with low socio-economic condition are most commonly suffering from abdominal tuberculosis.Journal of National Institute of Neurosciences Bangladesh, July 2022;8(2):162-166